High Prevalence of Esophageal Dysmotility in Asymptomatic Obese Patients - Justin Côté-Daigneault; Pierre Leclerc; Josette Joubert; Mickael Bouin (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Obesity is an important health problem affecting >500 million people worldwide. Esophageal dysmotility is a gastrointestinal pathology associated with obesity; however, its prevalence and characteristics remain unclear. Esophageal dysmotilities have a high prevalence among obese patients regardless of gastrointestinal symptoms.